1997
DOI: 10.4319/lo.1997.42.7.1492
|View full text |Cite
|
Sign up to set email alerts
|

Release and bioavailability of C, N, P Se, and Fe following viral lysis of a marine chrysophyte

Abstract: The potential importance of the viral lysis of phytoplankton for nutrient and carbon cycling has been acknowledged, but no quantitative assessments of this phenomenon exist. Radiotracer experiments examined the release and bioavailability of C, N, P Fe, and Se following viral lysis of the "brown tide" chrysophyte Aureococcus anophagefSeerens. Photochemical effects on the dissolved-particulate partitioning and biological uptake of virally released elements were also investigated. Viral lysis of A. anophagefSere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
237
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(252 citation statements)
references
References 64 publications
12
237
1
2
Order By: Relevance
“…This semi-closed trophic loop (Figure 2), fed externally by the release of DOM from phytoplankton and grazers, has the net effect of oxidizing organic matter and regenerating inorganic nutrients (Proctor and Fuhrman, 1991).Viral lysis of bacterial and phytoplankton cells removes a portion of autotrophic and microbial heterotrophic production from protozoan grazers providing, at the same time, a short circuit to the "traditional" concept of carbon cycling. It was even suggested that the recycling of organic material in a bacteriaphage-dissolved organic material loop could lead bacterial production to exceed primary production (Strayer, 1988;Gobler et al, 1997). From these results, the canonical view of the "microbial loop" as a way of loss of organic material from the particulate flux toward larger organisms, and the reincorporation of this organic material via heterotrophic bacteria (Azam et al, 1983), was upgraded with the "viral loop" as a subset.…”
Section: The Viral Loopmentioning
confidence: 70%
See 2 more Smart Citations
“…This semi-closed trophic loop (Figure 2), fed externally by the release of DOM from phytoplankton and grazers, has the net effect of oxidizing organic matter and regenerating inorganic nutrients (Proctor and Fuhrman, 1991).Viral lysis of bacterial and phytoplankton cells removes a portion of autotrophic and microbial heterotrophic production from protozoan grazers providing, at the same time, a short circuit to the "traditional" concept of carbon cycling. It was even suggested that the recycling of organic material in a bacteriaphage-dissolved organic material loop could lead bacterial production to exceed primary production (Strayer, 1988;Gobler et al, 1997). From these results, the canonical view of the "microbial loop" as a way of loss of organic material from the particulate flux toward larger organisms, and the reincorporation of this organic material via heterotrophic bacteria (Azam et al, 1983), was upgraded with the "viral loop" as a subset.…”
Section: The Viral Loopmentioning
confidence: 70%
“…Besides the already mentioned high levels of viral abundance and infection on bacteria, infection of phytoplankton is also common during intense episodes of coastal algal bloom (Proctor and Fuhrman, 1991;Yau et al, 2011;Shelford et al, 2012;Hasumi and Nagata, 2014;Stock et al, 2014). Consequently, viral lysis of phytoplankton can significantly affect the partitioning and biological cycling of elements such as C, N, P, Si, and Fe (Gobler et al, 1997), and the potential consequences of viral infection on nutrient cycling has been extensively discussed ever since (Bergh et al, 1989;Heldal and Bratbak, 1991;Proctor and Fuhrman, 1991;Suttle et al, 1991).…”
Section: Viruses and Phytoplankton Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that protistan grazing may be an additional source of iron binding ligands in seawater, through the regeneration of iron from bacterial biomass. Similar theories have been suggested for metazoan grazing (Hutchins & Bruland 1994) and viral lysis of cells (Gobler et al 1997). The binding strength and bioavailability of the putative iron ligands produced in our model systems is unknown.…”
mentioning
confidence: 64%
“…Viruses and virus-like particles (VLPs) have been discovered in a variety of phytoplankton and bacteria (48,54,64) and have been recognized as important agents in controlling bacterial and algal biomass (4,41,48) and nutrient cycling (17,66) and in maintaining the biodiversity of bacteria and microalgae (5,10,12). So far, more than 13 viruses infecting marine microalgae have been isolated and characterized (5).…”
mentioning
confidence: 99%